Dropout at primary and secondary level : a challenge to ensure rights to education for the Government of Bangladesh - Zaman, Md. Mostafa (BRAC University, 2016)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2014.